New formulation of Lyapunov direct method for nonautonomous real-order systems - Lenka, Bichitra Kumar; Bora, Swaroop Nandan (Nonlinear Analysis: Modelling and Control, 2025)
Lyapunov stability analysis of nonautonomous real-order systems is put forward here in the sense of Caputo in a new and different way. We introduce new theorems and inequalities that give stability of constant solutions in the domain of attraction to such systems when attached with random initial time placed on the real axis. We give some examples including an advanced nonlinear Lorenz system to illustrate the results.